Integrated assessment and influencing factor analysis of energy-economy-environment system in rural China - Shi Yin; Yuan Yuan (AIMS Energy)
With China's economic growth, energy-economy-environment (3E) issues in rural areas have become more prominent. As key areas for energy consumption and environmental protection, analyzing the influencing factors of the 3E system in rural areas is crucial. We constructed and analyzed the rural 3E model using clustering and examined the relationship between scientific and technological talent, the economic level of rural residents, and 3E development through principal component regression. The findings showed: (1) Overall improvement in 3E development, with coastal and non-coastal areas showing significant differences; (2) room for energy improvement, rapid economic growth, and more balanced environmental development in some regions; (3) scientific and technological talent and economic level significantly impacted 3E development; and (4) in coastal areas, talent development had a greater impact, while in non-coastal areas, both talent and economic development had comparable effects. Moreover, 1-unit increase in talent development in coastal areas boosted 3E development by 0.12 units, while in non-coastal areas, talent and economic level increased 3E development by 0.04 and 0.06 units, respectively.